2013
DOI: 10.1089/aid.2012.0254
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among HIV Infection, Metabolic Risk Factors, and Left Ventricular Structure and Function

Abstract: Our objective was to determine if the presence of metabolic complications (MC) conveyed an additional risk for left ventricular (LV) dysfunction in people with HIV. HIV⁺ and HIV⁻ men and women were categorized into four groups: (1) HIV⁺ with MC (43±7 years, n=64), (2) HIV⁺ without MC (42±7 years, n=59), (3) HIV⁻ with MC (44±8 years, n=37), or (4) HIV⁻ controls without MC (42±8 years, n=41). All participants underwent two-dimensional (2-D), Doppler, and tissue Doppler echocardiography. Overall, the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…To date, most studies of PA in HIV + individuals have focused on changes in body morphology and metabolism (Cade et al, 2013, 2008; Yarasheski et al, 2012, 2011). Only a few have investigated relationships between PA and cognition (Cade et al, 2013; Dufour et al, 2013; Fazeli et al, 2014; Gomes-Neto, Conceicao, Oliveira Carvalho, & Brites, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most studies of PA in HIV + individuals have focused on changes in body morphology and metabolism (Cade et al, 2013, 2008; Yarasheski et al, 2012, 2011). Only a few have investigated relationships between PA and cognition (Cade et al, 2013; Dufour et al, 2013; Fazeli et al, 2014; Gomes-Neto, Conceicao, Oliveira Carvalho, & Brites, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies of PA in HIV+ individuals have focused on changes in body morphology and metabolism (Cade et al, 2013, 2008; Yarasheski et al, 2012, 2011). Only a few have investigated relationships between PA and cognition (Cade et al, 2013; Dufour et al, 2013; Fazeli et al, 2014; Gomes-Neto, Conceicao, Oliveira Carvalho, & Brites, 2013). Two studies reported a positive correlation between PA and cognition in HIV+ individuals, however, PA was defined as any activity that increased heart rate over the previous 72 hr (Dufour et al, 2013; Fazeli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%